Isothiazolinones as causal factors of contact allergy epidemics in the 20th and 21st centuries - Dorota Chomiczewska-Skóra; Beata Kręcisz; Marta Kieć-Świerczyńska (Nofer Institute of Occupational Medicine, 2014)
Chloromethylisothiazolinone (MCI) and methylisothiazolinone (MI) have been widely used as preservatives in cosmetics, household products and industrial products since the late 1970s. First cases of contact allergy to the MCI/MI combination were noted in 1980-1982 in Sweden. Then, a significant increase in the frequency of sensitization to these compounds was observed in many European centers. The increase has been stopped by the introduction of legislation on their maximum concentrations in consumer and industrial products in Europe and in some non-European countries. But approval of the use of MI alone without limits in industrial products (from 2000) and at a maximum concentration of 100 ppm in cosmetics (from 2005) resulted in an unprecedented increase in the number of individuals sensitized to this compound. Allergic contact dermatitis due to MI occurs in both adults and children. It is often manifested by severe symptoms, which may be also induced by airborne exposure. The most important sources of sensitization include cosmetic products and paints. To counteract the increasing problem of contact allergy epidemic to MI, the recommendations have been developed, suggesting the ban on the use of MI in "leave-on" cosmetics and maximum concentration of 15 ppm in "rinse-off" products. These recommendations are likely to be implemented in 2014. Med Pr 2014;65(4):543-554